ChemInform Abstract: New Transition Metal Oxide Fluorides with ReO3‐Type Structure. Issue 32 (22nd July 2016) - Nakhal, Suliman; Lerch, Martin
Abstract: CrNb2 O4 F5, and Fe2 Nb3 O6 F9 are prepared by adding stoichiometric amounts of Cr(NO3 )3 or Fe(NO3 )3 to a HF solution of Nb2 O5 (15 h; drying at 80 °C, 2 d).